Multidrug Resistance and Plasmid Profiles of Escherichia coli Isolated from Lebanese Broiler Farms - Shaib, Houssam; Aoun, Paul; Ghaddar, Ahmad; Al Labadi, Hamza; Obeid, Youssef (International Journal of Microbiology, 2023)
The present study was undertaken to determine the antimicrobial resistance patterns and plasmid fingerprints of commensal Escherichia coli isolated from Lebanese broiler chickens. To that end, a total of 30 E. coli isolates were collected from 15 semi-open broiler farms from North Lebanon and Bekaa Valley. Results showed that all the isolates were resistant to at least nine out of 18 evaluated antimicrobial agents. The best-performing antibiotic families were Carbapenems (Imipenem) and Quinolones (Ciprofloxacin and Norfloxacin) to which only 0.0 and 8.3% of the isolates were resistant, respectively. Fifteen various plasmid profiles were depicted, and all the isolates were found to possess one or multiple plasmids. The plasmid sizes varied from 1.2 to 21.0 kbp, and the most commonly detected plasmid had a size of 5.7 kbp (23.3% of the isolates). There was no significant association between the number of plasmids per isolate and resistance to a particular drug. Nevertheless, the presence of specific plasmids, namely, the 2.2 or 7.7 kbp sized ones, was strongly correlated to Quinolones or Trimethoprim resistance, respectively. Both the 7.7 and 6.8 kbp plasmids showed mild correlation to Amikacin resistance, and the 5.7 kbp plasmid was mildly correlated to Piperacillin-Tazobactam resistance. Our findings highlight the need to revise the list of antimicrobials currently used in Lebanese poultry and associate the presence of specific plasmids to antimicrobial resistance patterns in E. coli isolates. The revealed plasmid profiles could also serve any future epidemiological investigation of poultry disease outbreaks in the country.